2019
DOI: 10.3389/fenrg.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Turbulent Flow and Heat Transfer in Internally Finned Tubes

Abstract: In this study, single-phase heat transfer enhancement in internally finned tubes is investigated numerically. The influence of fin number, helix angle, fin height, fin width, and shape on the flow and heat transfer characteristics is studied. The research results indicate that the resistance coefficient and Nusselt number both increase with the increment of these parameters, among which the helix angle has the largest impact on the heat transfer enhancement. In addition, the shape of fins also has a small effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Where t in and t out are the inlet and the outlet temperatures of cooling air, q V is the volume flow rate, ρ and c p are the density and the specific heat capacity of cooling air, respectively. Then, the Nusselt number is expressed as (Liu et al, 2019;Wang B. et al, 2020):…”
Section: Technological Notesmentioning
confidence: 99%
“…Where t in and t out are the inlet and the outlet temperatures of cooling air, q V is the volume flow rate, ρ and c p are the density and the specific heat capacity of cooling air, respectively. Then, the Nusselt number is expressed as (Liu et al, 2019;Wang B. et al, 2020):…”
Section: Technological Notesmentioning
confidence: 99%
“…The effects of different structure parameters (fin number, diameter, helix angle, width, and fin height) on the heat transfer performance were studied. Lie et al [14]. found that Nu and f both increased as the values of these parameters increased and that the helical angle had the strongest effect on the heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 97%